Autonomic dysfunction in COVID-19 patients receiving mechanical ventilation: A cross-sectional study - Silva, Renata Baltar da; Neves, Victor Ribeiro; Barros, Mayara Costa; Gambassi, Bruno Bavaresco; Schwingel, Paulo Adriano; Sobral-Filho, Dário Celestino (São Paulo Medical Journal, 2023)
BACKGROUND: Coronavirus disease 2019 (COVID-19) can damage cardiac tissue by increasing troponin levels and inducing arrhythmias, myocarditis, and acute coronary syndrome. OBJECTIVES: To analyze the impact of COVID-19 on cardiac autonomic control in mechanically ventilated intensive care unit (ICU) patients. DESIGN AND SETTING: This cross-sectional analytical study of ICU patients of both sexes receiving me-chanical ventilation was conducted in a tertiary hospital.METHODS: Patients were divided into COVID-19-positive (COVID(+)) and COVID-19-negative (COVID(-)) groups. Clinical data were collected and heart rate variability (HRV ) records obtained using a heart rate monitor. RESULTS: The study sample comprised 82 subjects: 36 (44%) in the COVID(-) group (58.3% female; me-dian age, 64.5 years) and 46 (56%) in the COVID(+) group (39.1% females; median age, 57.5 years). The HRV indices were lower than the reference values. An intergroup comparison identified no statistically significant differences in the mean normal-to-normal (NN) interval, standard deviation of the NN interval, or root mean square of successive differences in NN intervals. The COVID(+) group had an increased low frequency (P = 0.05), reduced high frequency (P = 0.045), and increased low frequency/high frequency (LF/HF) ratio (P = 0.048). There was a weak positive correlation between LF/HF and length of stay in the COVID(+) group.CONCLUSION: Patients who received mechanical ventilation had lower overall HRV indices. COVID(+) pa-tients who received mechanical ventilation had lower vagal HRV components. These findings likely indicate clinical applicability, as autonomic control impairments are associated with a greater risk of cardiac death.